Diseño y construcción de una máquina para balanceo dinámico de rotores hasta 250 kg. en la empresa NDT-PDM Ecuador - Cruz Loya, Edwin Vinicio (2017)
The development of the research project with the concepts used in the field of vibration analysis and specifically with the dynamic balance, the main motivation for the implementation this machine requires a high amount of rotating equipment in the industry, which by the nature of their work generate centrifugal forces and these in turn mechanical vibrations that derive in premature failure in the settlements and deterioration in them. The centrifugal forces are caused by the imbalance of the bodies, which can be corrected before the installation of rotary equipment in the machines, these corrections are made with dynamic balancing machines, becoming a necessary resource for rotary equipment; But because of the fact that these machines are not manufactured in the country and their import costs are high, it is proposed to implement a balance bank that usually adapts to the needs requested by the company. Previously mentioned Correction of the imbalance is essential in a rotating equipment and the sea for the perfect operation, its maintenance both preventive and corrective, so the company's vision with this balance bank is to provide the service anywhere in the country or the Continent and sea with rotors of at least 50 kilograms and a maximum of 2 tons. For this the rolling machine will be able to be transported and provide on-site service. Finally, we analyze the results obtained and conclude on the practical application of the methods used and compared.